Melatonin Treatment Delays Senescence and Maintains the Postharvest Quality of Baby Mustard (Brassica juncea var. gemmifera) - Di, Hongmei; Li, Zhiqing; Wang, Yating; Zhang, Yi; Bian, Jinlin; Xu, Jingyi; Zheng, Yangxia; Gong, Ronggao; Li, Huanxiu; Zhang, Fen; Sun, Bo (Frontiers in Plant Science, 2022)
The effect of melatonin treatment on the visual quality and content of health-promoting compounds in baby mustard (Brassica juncea var. gemmifera) at 20°C was investigated in this study. Application of 100 μmol L-1 melatonin was the most effective in prolonging the shelf life of baby mustard among all of the concentrations tested (1, 50, 100, and 200 μmol L-1). The 100 μmol L-1 melatonin treatment also delayed the increase in weight loss and the decrease in sensory parameter scores; retarded the decline of chlorophyll content; slowed the decline in antioxidant capacity by maintaining the content of carotenoids and ascorbic acid, as well as increasing the levels of total phenolics; and increased the content of individual and total glucosinolates in the lateral buds of baby mustard. These findings indicate that melatonin treatment is effective for maintaining the sensory and nutritional qualities of postharvest baby mustard.